Regulation and directed inhibition of ECP production by human neutrophils - Vega-Rioja, Antonio; Chacón, Pedro; Fernández-Delgado, Lourdes; Doukkali, Bouchra; del Valle Rodríguez, Alberto; Perkins, James R.; Ranea, Juan A. G.; Dominguez-Cereijo, Leticia; Pérez-Machuca, Beatriz María; Palacios, Ricardo; Rodríguez, David; Monteseirín, Javier; et al. (Frontiers in Immunology, 2022)
Background: Neutrophils are involved in the pathophysiology of allergic asthma, where the Eosinophil Cationic Protein (ECP) is a critical inflammatory mediator. Although ECP production is attributed to eosinophils, we reported that ECP is also present in neutrophils from allergic patients where, opposite to eosinophils, it is produced in an IgE-dependent manner. Given the key role of ECP in asthma, we investigated the molecular mechanisms involved in ECP production, the effect induced by agonists and widely used clinical approaches. We also analyzed the correlation between ECP production and lung function. Methods: Neutrophils from allergic asthmatic patients were challenged with allergens, alone or in combination with cytokines, in the presence of cell-signaling inhibitors and clinical drugs. ECP levels were analyzed by ELISA and confocal microscopy. Lung function was assessed by spirometry. Results: IgE-mediated ECP release is dependent on the phosphoinositide 3-kinase, the extracellular signal-regulated kinase (ERK1/2) and the production of reactive oxygen species by the NADPH-oxidase. The calcineurin phosphatase and the transcription factor NFAT are also involved. ECP release is enhanced by the cytokines interleukin (IL)-5 and granulocyte macrophage-colony stimulating factor, and inhibited by interferon-gamma, IL-10, clinical drugs (formoterol, tiotropium and budesonide) and allergen-specific IT. We also found an inverse correlation between asthma severity and ECP levels. Conclusions: Our results describe the molecular pathways involved in the ECP production and potential therapeutic targets. We also provide a new method to evaluate the disease severity in asthmatic patients based on the quantification of the in vitro ECP production by peripheral neutrophils.